2014
DOI: 10.1115/1.4027910
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Dynamics Study on Heat Transfer Characteristics Over the Interface of Self-Assembled Monolayer and Water Solvent

Abstract: We performed molecular dynamics (MD) simulations of the interface which is comprised of self-assembled monolayer (SAM) and water solvent to investigate heat transfer characteristics. In particular, local thermal boundary conductance (TBC), which is an inverse of so-called Kapitza resistance, at the SAM-solvent interface was evaluated by using the nonequilibrium MD (NEMD) technique in which the one-dimensional thermal energy flux was imposed across the interface. By using two kinds of SAM terminal with hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…Therefore, the reduction of TBR at the solid/polymer interface is caused not by an increase in the amount of adsorbed polymer but only by the improved affinity due to the enhancement of electrostatic interaction between the charged surface and the adsorbed polymer. Similar results have been reported for gold–SAM–water system. In such a system, the interfacial thermal conductance across the SAM/water interface improved with increasing polarity of the SAM because more polar functionalized surface can lead to stronger electrostatic interaction across the SAM/water interface.…”
Section: Resultssupporting
confidence: 81%
“…Therefore, the reduction of TBR at the solid/polymer interface is caused not by an increase in the amount of adsorbed polymer but only by the improved affinity due to the enhancement of electrostatic interaction between the charged surface and the adsorbed polymer. Similar results have been reported for gold–SAM–water system. In such a system, the interfacial thermal conductance across the SAM/water interface improved with increasing polarity of the SAM because more polar functionalized surface can lead to stronger electrostatic interaction across the SAM/water interface.…”
Section: Resultssupporting
confidence: 81%
“…Considering the vibrational spectra, previous simulation work 21,22 shows that the vibrational spectra of alkanethiols are in between of the spectra of Au and organic solvent in the low frequency regime so the matching is better for SAM-modified interfaces. In other words, the SAMs serve as a bridge between Au and ethanol and facilitate thermal transport.…”
mentioning
confidence: 99%
“…Understanding nanoscale heat transfer across hard–soft material interfaces, e.g., solid–polymer and solid–liquid interfaces, is of great importance for improving the reliability of nanoelectronic systems where efficient heat dissipation becomes critical. Key quantities that thermally characterize a given dissimilar interface are the interfacial thermal conductance G = q / Δ T sl , with q the heat flux and Δ T sl the temperature difference at the interface, and the associated thermal heat (Kapitza) resistance R = 1/ G . Over the past decade, considerable efforts have been devoted to directly probing G or R through both experiments and molecular simulations. Research groups have attempted to find a correlation between G and other quantities that characterize solid–liquid interfaces. Shenogina et al reported a correlation between G for interfaces between water and hydrophilic and hydrophobic substrates and the work of adhesion W adh of these interfaces .…”
mentioning
confidence: 99%